PELATIHAN SOFTWARE AKUNTANSI DENGAN TOPIK RMA, CASH & BANK, DAN GENERAL LEDGER DI KRISTOFORUS I JAKARTA - Chelsya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2026)
The development of infoRMAtion technology and the development of industry 4.0, provides convenience for companies in running their businesses, procurement of bookkeeping, financial reporting, and interpretation of financial reports. In bookkeeping and financial reporting, many companies use the help of accounting software, so that companies can focus more on determining strategies and making decisions that will bring profits. The application of Accurate software requires special competencies, so it is very important for companies to provide training to their employees so that they can apply Accurate software well. The purpose of Accurate software training is to improve students' expertise competencies, and students can produce Accurate and reliable financial reports. The reason the author held Accurate software training at Kristoforus High School was because of the problems faced by partners, namely students had never received software-based accounting training either in the school curriculum or in extracurricular activities, so that students did not have competent skills in applying accounting software. The partner's problems above are described as: (1) Definition of Accurate software; (2) Benefits of Accurate software; (3) Features in Accurate software; (4) Operation of Accurate software features RMA, Cash & Bank, and General Ledger. Accurate software training is carried out using the following methods: (1) Planning, (2) Implementation of PKM using educational methods and training methods, (3) Evaluation of results using pre-test and post-test quizzes, (4) Evaluation of partner satisfaction through questionnaires, (5) Dissemination of results through scientific publications. The outputs produced are scientific publication journals, IPR certificates, and posters. Perkembangan teknologi informasi dan perkembangan industri 4.0, memberikan kemudahan bagi perusahaan dalam menjalankan usahanya, pengadaan pembukuan, pelaporan keuangan, dan interpretasi laporan keuangan.. Dalam pembukuan dan pelaporan keuangan, banyak perusahaan menggunakan bantuan software akuntansi, sehingga perusahaan dapat lebih fokus pada penetapan strategi dan pengambilan keputusan yang akan mendatangkan keuntungan.. Pengaplikasian software Accurate membutuhkan kompetensi khusus, sehingga penting sekali bagi perusahaan untuk memberikan pelatihan kepada karyawannya agar dapat mengaplikasi software Accurate dengan baik. Tujuan pelatihan software Accurate adalah untuk meningkatkan kompetensi keahlian siswa, serta siswa dapat menghasilkan pelaporan keuangan yang akurat dan dapat diandalkan (reliable). Alasan penulis mengadakan pelatihan software Accurate di SMA Kristoforus adalah karena peRMAsalahan yang dihadapi oleh mitra, yaitu siswa-siswa belum pernah menerima pelatihan akuntansi berbasis software baik di dalam kurikulum sekolah maupun dalam ekstrakulikuler, sehingga siswa-siswa tidak memiliki keahlian kompeten dalam mengaplikasikan software akuntansi. PeRMAsalahan mitra di atas dijabarkan menjadi: (1) Definisi software Accurate; (2) Manfaat software Accurate; (3) Fitur-fitur yang ada di software Accurate; (4) Pengoperasian software Accurate fitur RMA, Cash & Bank, dan General Ledger. Pelatihan software Accurate dilaksanakan dengan metode sebagai berikut: (1) Perencanaan, (2)Pelaksanaan PKM dengan menggunakan metode edukasi dan metode pelatihan, (3) Evaluasi hasil menggunakan kuis pre test dan post test, (4) Evaluasi kepuasan mitra melalui kuesioner, (5) Diseminasi hasil melalui publikasi ilmiah. Luaran yang dihasilkan yaitu jurnal publikasi ilmiah, sertifikat HKI, dan poster.